Extremophiles as Plant Probiotics to Promote Germination and Alleviate Salt Stress in Soybean - Ana P. Santos; Carolina Belfiore; Cristina Úrbez; Alejandro Ferrando; Miguel A. Blázquez; María E. Farías (Journal of Plant Growth Regulation, 2023)

Correction to: Characterization of novel pollen-expressed transcripts reveals their potential roles in pollen heat stress response in Arabidopsis thaliana - Nicholas Rutley; Laetitia Poidevin; Tirza Doniger; Richard L. Tillett; Abhishek Rath; Javier Forment; Gilad Luria; Karen A. Schlauch; Alejandro Ferrando; Jeffery F. Harper; Gad Miller (Plant Reproduction, 2021)

Characterization of novel pollen-expressed transcripts reveals their potential roles in pollen heat stress response in Arabidopsis thaliana - Nicholas Rutley; Laetitia Poidevin; Tirza Doniger; Richard L. Tillett; Abhishek Rath; Javier Forment; Gilad Luria; Karen A. Schlauch; Alejandro Ferrando; Jeffery F. Harper; Gad Miller (Plant Reproduction, 2021)
Key message Arabidopsis pollen transcriptome analysis revealed new intergenic transcripts of unknown function, many of which are long non-coding RNAs, that may function in pollen-specific processes, including the heat stress response. Abstract The male gametophyte is the most heat sensitive of all plant tissues. In recent years, long noncoding RNAs (lncRNAs) have emerged as important components of cellular regulatory networks involved in most biological processes, including response to stress. While examining RNAseq datasets of developing and germinating Arabidopsis thaliana pollen exposed to heat stress (HS), we identified 66 novel and 246 recently annotated intergenic expressed loci (XLOCs) of unknown function, with the majority encoding lncRNAs. Comparison with HS in cauline leaves and other RNAseq experiments indicated that 74% of the 312 XLOCs are pollen-specific, and at least 42% are HS-responsive. Phylogenetic analysis revealed that 96% of the genes evolved recently in Brassicaceae . We found that 50 genes are putative targets of microRNAs and that 30% of the XLOCs contain small open reading frames (ORFs) with homology to protein sequences. Finally, RNAseq of ribosome-protected RNA fragments together with predictions of periodic footprint of the ribosome P-sites indicated that 23 of these ORFs are likely to be translated. Our findings indicate that many of the 312 unknown genes might be functional and play a significant role in pollen biology, including the HS response.

Involvement of polyamines in plant response to abiotic stress - Rubén Alcázar; Francisco Marco; Juan C. Cuevas; Macarena Patron; Alejandro Ferrando; Pedro Carrasco; Antonio F. Tiburcio; Teresa Altabella (Biotechnology Letters, 2006)

A Specific Real-Time Quantitative PCR Detection System for Event MON810 in Maize YieldGard® Based on the 3′-Transgene Integration Sequence - Marta Hernández; Maria Pla; Teresa Esteve; Salomé Prat; Pere Puigdomènech; Alejandro Ferrando (Transgenic Research, 2003)